1997
DOI: 10.2169/internalmedicine.36.790
|View full text |Cite
|
Sign up to set email alerts
|

Portal-hepatic Venous Shunt through a Portal Aneurysm Complicated by Hepatic Encephalopathy and Pulmonary Hypertension.

Abstract: Wereport a rare case of portal-hepatic venous shunt through an enormousportal aneurysm complicated by pulmonary hypertension. A 66-year-old womanwas admitted to our hospital for hepatic encephalopathy. Chest roentgenography revealed pulmonary hypertension. Computed tomography and ultrasound examination demonstrated a shunt between the portal and hepatic veins through an enormousportal aneurysm. The diagnoses of portal-hepatic venous shunt and pulmonaryhypertension were confirmed by hepatic venous catheterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In our second case, multiple small vessels connected the umbilical portion of the portal vein with the DV. One other case of this type has been reported in the literature 7) . This pattern is similar to cavernous transformation resulting from occlusion of the portal vein, and may be collateral pathway due to occlusion of the DV in utero.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In our second case, multiple small vessels connected the umbilical portion of the portal vein with the DV. One other case of this type has been reported in the literature 7) . This pattern is similar to cavernous transformation resulting from occlusion of the portal vein, and may be collateral pathway due to occlusion of the DV in utero.…”
Section: Discussionmentioning
confidence: 89%
“…An anomalously dilated DV larger than 4 mm in diameter is rarely seen with or without cardiac anomaly (5 such cases among 293 infants under 10 weeks of age with patent DV were reported by Farrant) 2) . Although patent DV is congenital, age at onset of symptoms due to hyperammonemia varies in adults from 29 to 66 years of age 3,4,7,9,12) , possibly because of variability in the shunt ratio and individual tolerance to ammonia. Patent DV is considered an intrahepatic type of portosystemic shunt, that connects the portal vein at its umbilical portion and the junction of the left hepatic vein and inferior vena cava.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated an association between intrahepatic portacaval shunts and neonatal jaundice, congenital heart disease, congenital biliary atresia, polycystic ovary syndrome, pelvic myoma, coronary artery fistulas, hemangiomas, and membranoproliferative glomerulonephritis, focal nodular hyperplasia, hereditary hemorrhagic telangiectasia (Osler-Weber-Rendu syndrome), and pulmonary hypertension due to vasoconstrictive agents bypassing metabolism in the liver [10, 14, 15, 16, 17, 18, 19]. Only one other case in the literature describes a truly asymptomatic portacaval shunt with morphology such as seen in our patient [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether these shunts represent an aberrant ductus venosus or an anomalous vessel in addition to a functional ductus venosus that closes before diagnosis 9,10 . In humans, intrahepatic shunts that are connected to a hepatic vein before draining into the caudal vena cava are called porto‐ or portal‐hepatic venous shunts 11,12 …”
Section: Introductionmentioning
confidence: 99%